Prison Birth Project: A3 Initiative (Assessment, Awareness, and Activism) - Sokolov, Rachel (2019)
The mission of the Prison Birth Project is to connect students at the University of Michigan with people who have been incarcerated so as to advocate for their human rights. My team and I are striving to serve a population of incarcerated women during their pregnancy and deliver their children behind bars so that they may feel supported during their birth and postpartum processes. We aim to humanize incarcerated women's experiences and inform others on how to respect them within a healthcare setting. We will conduct a survey that will allow us to assess campus beliefs, attitudes, and knowledge about topics like mass incarceration, restorative justice, and childbirth rights. The survey would inform my team and me as to how to best educate the community and raise awareness about these issues. We hope to prepare students who plan on pursuing a career in the medical field to work with incarcerated patients. Ginsberg MESA SAMI https://deepblue.lib.umich.edu/bitstream/2027.42/148855/1/Sokolov.pdf